Analysis of Genetic Profiles of Heavy Metal Phytoremediator Plants From Gold Mining Areas - Sih Winarti; Liswara Neneng; Yohanes Edy Gunawan; Chaidir Adam (Bioscience, 2020)
The resistance and survival ability of phytoremediator plants in a polluted environment is thought to be a form of genetic adaptation. This research aimed: (1) to identify the dominant plant species in ex-gold mining area; (2) to analyze the genetic profile of phytoremediator plants from ex-gold mining area; and (3) to compare the genetic profile of heavy metal phytoremediator plants from ex-gold mining area with the same plant species from non-mining area. The samples of this study were Cyperus sp., Lycopodium sp., and Melastoma sp. The research procedures carried out include sample collection, DNA isolation, DNA amplification with PCR, and DNA visualization with Electrophoresis. The results show that the dominant plant species of ex-gold mining area are Cyperus sp., Lycopodium sp., and Melastoma sp. The genetic profile analysis of dominant plant species of ex-gold mining area show that no DNA bands appeared from the target gene as the result of amplification using specific primers of Metallothionein gene. The result of RAPD analysis using OPA-04 universal primers show that at 500-750 bp there are differences in DNA bands that appeared between the samples. DNA bands that appeared in the genetic profile of phytoremediator plants is thought to be the representation of the gene that responsible for heavy metals tolerance.